Modern approach to primary cervical cancer screening (literature review) - O. V. Turanova; T. E. Belokrinitskaya; N. I. Frolova; E. V. Kayukova (Acta Biomedica Scientifica, 2018)
The problem of morbidity and mortality from cervical cancer is one of the leading in the world medical practice. Many countries began to reconsider the approach to primary screening for cervical cancer after etiological role of human papillomavirus (HPV) in cervical carcinogenesis was determined. Most studies have shown that the identification of HPV DNA has a high prognostic value and can be used both as a co-testing and a primary test. However, the unwillingness of many women to visit a gynecologist due to subjective reasons makes it difficult to implement programs on prevention of cervical cancer. Women associate their unwillingness with the lack of time, discomfort and sickliness, a feeling of shame and confusion, when performing a vaginal examination. To solve this problem, in recent years, self-sampling systems for HPV-testing were devised. Self-sampling systems for HPV-testing are comparable with taking cervical sampler by a doctor; they increase the participation of women in cervical screening. Countries have a reduction in morbidity and mortality from cervical cancer due to the inclusion of the HPV-test in national screening programs. At present, many countries consider the introduction of self-sampling devices for vaginal content for HPV-testing in cervical screening. HPV-self-sampling has the potential to improve participation in screening programs, to reduce socioeconomic barriers to care and to improve the subjective patient experience.